The Blood of Patriots: Symbolic Violence and "The West". Issue 3 (27th May 2019) - Vitolo-Haddad, CV
Abstract : This article considers how demagoguery gives meaning to violence by providing a symbolic, expressive outlet for resentment resulting from real or felt precarity. This rhetorical process redirects frustrations away from the entities and sociopolitical structures responsible for creating precarity and toward a scapegoat. Rather than examining demagoguery as rhetoric produced by an individual rhetor or consumed by an audience of the masses, the author explores the "meso-level" of demagogic discourse: the organizations called into existence and motivated by individuals' shared identification with a symbolic struggle against an imagined Other. This phenomenon is illustrated through a close reading of the Proud Boys, a multinational fraternal organization that uses an aesthetic of libertarianism to advance a fascist politic.